The Impact of Kampus Merdeka Policy on Entrepreneurship Education: A Qualitative Study of Quality Graduate Development - Rahmatillah, Rahmatillah; Hendra, Hendra; Darmawan, Wahyu (Islamic Educational Management Programme, 2023)
Entrepreneurship values play a fundamental role in the development of high-quality and sustainable higher education institutions. The effectiveness of educational outcomes is assessed through their contribution to creating competitive value, particularly in relation to industry and workforce needs. The government's Kampus Merdeka program provides opportunities for Islamic higher education institutions to foster innovation. This research aims to analyze entrepreneurship management within the context of the Kampus Merdeka policy to produce quality graduates. The study adopts an interpretative paradigm and employs qualitative literature review techniques (library research). Data sources for this research consist of 50 academic journals and other scholarly writings. The findings of this study are as follows: Kampus Merdeka encourages students to cultivate entrepreneurial interests; students can develop their potential based on their interests and talents, enabling them to pursue careers aligned with their expertise; Kampus Merdeka instills a competitive mindset and fosters a conservative thinking paradigm; Kampus Merdeka revitalizes the higher education system, making it more flexible, innovative, and technology-adaptive; Entrepreneurship values are reinforced through the enhancement of academic culture and a series of strategic policies.